The first search for extremely-high energy cosmogenic neutrinos with the IceCube Neutrino Observatory - Collaboration, I; Abbasi, R; Abdou, Y; Abu-Zayyad, T; Adams, J; Aguilar, J; Ahlers, M; Andeen, K; Auffenberg, J; Bai, X; Baker, M; Barwick, S; et al. (2010)
We report on the results of the search for extremely-high energy (EHE) neutrinos with energies above $10^7$ GeV obtained with the partially ($\sim$30%) constructed IceCube in 2007. From the absence of signal events in the sample of 242.1 days of effective livetime, we derive a 90% C.L. model independent differential upper limit based on the number of signal events per energy decade at $E^2 φ_{ν_e+ν_μ+ν_τ}\simeq 1.4 × 10^{-6}$ GeV cm$^{-2}$ sec$^{-1}$ sr$^{-1}$ for neutrinos in the energy range from $3×10^7$ to $3×10^9$ GeV.